Improving assessment and management of large non-pedunculated colorectal lesions in a Western center over 10 years: lessons learned and clinical impact - Vanella, Giuseppe; Coluccio, Chiara; Antonelli, Giulio; Angeletti, Stefano; Micheli, Federica; Barbato, Antonio; De Rossi, Gaia; Marchetti, Alessandro; Mereu, Elena; Pepe, Paola; Corleto, Vito Domenico; D’Ambra, Giancarlo; Ruggeri, Maurizio; Di Giulio, Emilio (Endoscopy International Open, 2020)
Background and study aims Outcomes of endoscopic assessment and management of large colorectal (CR) non-pedunculated lesions (LNPLs) are still under evaluation, especially in Western settings. We analyzed the clinical impact of changes in LNPL management over the last decade in a European center.Patients and methods All consecutive LNPLs ≥ 20 mm endoscopically assessed (2008–2019) were retrospectively included. Lesion, patient, and resection characteristics were compared among clinically relevant subgroups. Multivariate logistic regression (for predictors of submucosal invasion [SMI] and recurrence), Kaplan-Meier curves and ROC curves (for temporal cut-offs in trends analyses) were used. Results A total of 395 LNPLs were included (30 mm [range 20–40]; SMI = 9.6 %; primary endoscopic resection [ER] = 88.4 %). Pseudo-depression and JNET classification independently predicted SMI beyond single morphologies/location. After complete ER, involvement of ileocecal valve/dentate line, piece-meal resection and high-grade dysplasia independently predicted recurrence. Rates of 5-year recurrence-free, surgery-free and cancer-free survival were 77.5 %, 98.6 % and 100 %, respectively, with 93.8 % recurrences endoscopically managed and no death attributable to ER or CR cancer (versus 3.4 % primary surgery mortality).ROC curves identified the period ≥ 2015 (following Endoscopic Submucosal Dissection [ESD] introduction and education on pre-resective lesion assessment) as associated with improved lesions’ characterization, increased en-bloc resection of SMI lesions (87.5 % vs 37.5 %; p = 0.0455), reduced primary surgery (7.5 % vs 16.7 %; p = 0.0072), surgical referral of benign lesions (5.1 % vs 14.8 %; p = 0.0019), and recurrences.Conclusions ESD introduction and educational interventions allowed ER of more complex lesions, offset by increased complementary surgery for complications or intrinsic histological risk. Nevertheless, overall, they have reduced surgery demand and increased appropriateness and safety of LNPL management in our center.